Nasopharyngeal Carriage And Antimicrobial Sensitivity Of M. Catarrhalis From Healthy Subjects - Halil Ozerol, Ibrahim; Asgin, Nergis; Durmaz, Bengul; Tayyar Kalcioglu, M. (Annals of Medical Research, 2021)
None
Keywords: M.catarrhalis, Beta Lactamase, Upper Respiratory Infections